Maternidade e desamparo: um estudo psicanalítico - Flesh, Rachel (2021)
Motherhood is a unique experience in a woman's life, yet we know that it is surrounded by complexity. It involves both affection and the woman's place in society. Knowing that women have been conquering more space, it was necessary to study what is still little talked about. Pregnancy would be the starting point for this new phase, which begins with physical changes. Besides the physical transformations, the body calls the psyche to change, so that the woman goes through an intense pulsional investment. Pregnancy would be a period surrounded by feelings, issues and conflicts, among them, the fear of the baby, the mourning for the lost woman, once a daughter and now a mother, and the possibility of reworking childhood conflicts stand out. This from the conception of motherhood for psychoanalysis. Thus, considering the ambivalent feelings that surround maternity and other psychic aspects, this study made an articulation with the Freudian concept of helplessness. This concept is characterized as being a structuring condition of the psychism, that is, an insurmountable condition in which, when faced with a state of excess excitations, one seeks total discharge. To deal with this, we talk about the management of helplessness, which would be the way to build destinations for the drive. Then, from the literary illustration, “Mãe recém-nascida” (2019), "Newborn Mother", as a free translation, it became possible to articulate these concepts. Since it is noted that this phase of the beginning of motherhood could be understood as the birth of the mother herself. Finally, it is worth pointing out that for this study, searches were made in different databases, searching for books, texts and articles on the topic